2014
DOI: 10.1521/bumc.2014.78.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism dimensions as predictors of symptom dimensions of obsessive-compulsive disorder

Abstract: The correlation between obsessive-compulsive disorder (OCD) and perfectionism is well documented, yet it remains unclear if dimensions of perfectionism vary as a function of OCD symptom dimensions. To this end, the present study investigated the unique associations between dimensions of perfectionism (i.e., concern over mistakes, doubts about actions, personal standards, parental criticism, parental expectations, and organization) and OCD symptom dimensions (i.e., hoarding, washing, checking, ordering, obsessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Indeed, Hill et al (2004) found that these subscales of perfectionism are related to somatic complaints, depression, obsessivecompulsive symptomology, anxiety, interpersonal sensitivity, hostility, paranoia, and psychoticism. This pattern is consistent with the theoretical notion that perfectionism is maladaptive and is associated with mental illnesses, such as depression, anxiety, eating disorders, and obsessive-compulsive disorder (e.g., Sassaroli et al 2008;Egan et al 2011;Martinelli et al 2014). Step two 0.31 In contrast, organization was modestly positively correlated with life satisfaction in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, Hill et al (2004) found that these subscales of perfectionism are related to somatic complaints, depression, obsessivecompulsive symptomology, anxiety, interpersonal sensitivity, hostility, paranoia, and psychoticism. This pattern is consistent with the theoretical notion that perfectionism is maladaptive and is associated with mental illnesses, such as depression, anxiety, eating disorders, and obsessive-compulsive disorder (e.g., Sassaroli et al 2008;Egan et al 2011;Martinelli et al 2014). Step two 0.31 In contrast, organization was modestly positively correlated with life satisfaction in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Given the strong relationship between OCD and perfectionism (Martinelli et al, 2014), it is perhaps not surprising that scores on the FMPS and the CPQ were significantly correlated with mental contamination. Clinically, patients with mental contamination fears often present with extremely high moral standards which may be why they are more likely to interpret their intrusive thoughts as repugnant and unwanted .…”
Section: Discussionmentioning
confidence: 99%
“…More recently the term 'clinical perfectionism' has been described as "the overdependence of self-evaluation on the determined pursuit of personally demanding self-imposed standards in at least one highly salient domain despite adverse consequences" (Shafran, Cooper, & Fairburn, 2002, p.778). Although several studies report a strong relationship between OCD and perfectionism (see Martinelli, Chasson, Wetterneck, Hart, & Björgvinsson, 2014), it should be noted that one of the subscales of perfectionism ('Doubts About Actions') on the commonly used Frost Multidimensional Perfectionism Measure (Frost et al, 1990) was actually taken directly from the Maudsley Obsessive Compulsive Inventory (Hodgson & Rachman, 1977), a measure of OCD. Studies showing associations between this subscale and OCD severity (e.g., Martinelli et al, 2014) are therefore really demonstrating the overlap in symptoms between OCD and perfectionism.…”
Section: It Is Commonly Acknowledged When Diagnosing and Classifying mentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, perfectionism has become an important predictor of obsessive-compulsive symptoms (Martinelli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%